The effect of self-care training in reducing the epileptic seizure attacks of epileptic patients - T Hakimi gilani; S Nikpour; ES Hajikazemi; M Mahmoodi (Iran University of Medical Sciences, 1995)
This research is a quasi, experimental study in order to especify the effect of self-care training in reducing the epileptic seizures appearing in the epileptic patients referred to nerves clinics of the Medical science universities hospitals related to the Ministry of health, remedy and medical training of the city of Tehran in the year (1993-94) This research is done on a random basis on 68 epileptic patients suffering from the grandma epilepsy who have been referred to 5 nerves clinics. A 3-sections questionaire was completed by each patient at the presence of the researcher. 2 sections of which were designed to especify the individual especifications and the number of seizures appearing during 6 months before training, after appearance of seizure, and the kind of accidents created during the seizure. Then the neccessary coordination for a class establishment was organized with the subject group and the self care training class was held descriptively. later an educational booklet was given to the subject group.Three months after training, the third section of the questionaire which was included in the number of the seizures appearing during 3 months after the self care training, the reason and the kind of accidents created during the seizures, was completed by the units being researched and finally the findings were arranged in 29 tables. In reply to the second 'goal of the research: "to especify and to compare the number of seizures appearing during 6 months before self-care training in the subject group with the witness group at the same time, findings presented that majority of the units under research had 3-4 seizures and the comparison of the averages of seizures for both subject and witness group revealed no meaningful difference. And in reply to the third goal: "to especify the effect of self-care training through defining and comparing the occurances of seizures appearing in the same time in the subject and witness group during 3 months after self-care training and to test the research hypotheses" findings revealed that the majority of the subject group had 1-2 attacks while the majority of the withness group had 3-4. The comparison of the average number of attacks for both groups during 3 months, revealed a demographic meaningful difference and thus the hypotheses of the research was proved. In other words, the self-care training was effective in reducing the numbers of epileptic seizures appearance. In reply to the fourth goal "the reason behind appearance of seizures and the kind of accidents created during the attack along 6 months before and 3 months after the self-care training", findings confirmed that the most occurances of epileptic seizures were because of a stop or a change in drug usage, and the accident were mostly of the head stroke kind. In reply to the fifth goal "to especify the correlation between the individual characteristics and number of epileptic attacks in SUbject and withness group after self-care training". Demographic tests revealed no meaningful correlation. Based on the findings, suggestions for further research and implementations of the findings in different areas of health care practice were made